A new species of Campomanesia (Myrtaceae) from Bahia, Brazil, and its relationships with the C. xanthocarpa complex - Oliveira, Marla Ibrahim Uehbe; Landrum, Leslie Roger; Oliveira, Reyjane Patrícia; Funch, Ligia Silveira (Phytotaxa, 2013)
Results of studies with multiple approaches involving a species complex which includes Campomanesia xanthocarpa (Myrtaceae) indicate that specimens collected in Morro do Chapéu, the northern region of the Chapada Diamantina, Bahia, are distinct from those distributed farther south in Brazil. A description, comments, distribution map and an illustration of the new species, C. costata, are provided herein.